Avaliação in vitro das atividades biológicas da apitoxina extraída de Apis mellifera do semiárido - Viana, Geysa Almeida (Universidade Federal Rural do Semi-Árido, 2015)
Those from bee products have offered important contributions to human civilization and economy, and among the bee products bee venom is perhaps the most intriguing because of its healing properties. It consists of a complex mixture, and among its components the ones that stand out are melittin and phospholipase A2, which together represent about 75% of its dry weight. Melittin has significant therapeutic potential in the treatment of various diseases, in addition to being currently widely used in cosmetics as an aid in the retardation of aging. In this study, the bee venom samples of Apis mellifera bees obtained from the Rio Grande do Norte semiarid, were quantified as the total phenols and their biological activities in vitro were investigated, namely: antioxidant activity by the ability of the free radical scavenger (DPPH); antibacterial activity by diffusion in agar and antitumor activity by colorimetric MTT method. The content of total phenols obtained sample were 3.79 ± 0.3 mg / g and 0.37%, with high antioxidant capacity with a percentage of 92.59 ± 0.48%.. In relation to the antibacterial activity of bee venom Apis mellifera had a positive effect against the three strains tested being more active against Klebisiella pneumoniae bacterium, which was the most sensitive, and Staphylococcus aureus the most resistant. In relation to antitumor potential, bee venom showed significant cytotoxic activity against tumor cell lines HCT-116 (human colorectal carcinoma), HL-60 (human promyelocytic leukemia) and MDAMB435 (Melanoma), having a higher selectivity for the lines HCT-116 and HL-60. Finally, it was concluded that the bee Apis mellifera bee venom obtained in the semi-arid region may be used in non-conventional medicine as an antioxidant, antibacterial and cytotoxic agent. Key-words: bee venom, antioxidant, antibacterial, antitumor
Keywords: Veneno da abelha; Antioxidande; Antibacteriana; Antitumoral; CIENCIAS AGRARIAS::MEDICINA VETERINARIA